Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0121136
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase Expression Increases the Survival and Malignancy of Estrogen Receptor Positive Breast Cancer Cells

Abstract: In postmenopausal women, local estrogen produced by adipose stromal cells in the breast is believed to support estrogen receptor alpha (ERα) positive breast cancer cell survival and growth. This raises the question of how the ERα positive metastatic breast cancer cells survive after they enter blood and lymph circulation, where estrogen level is very low in postmenopausal women. In this study, we show that the aromatase expression increased when ERα positive breast cancer cells were cultured in suspension. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…The spontaneously immortalized human mammary epithelial MCF-10A cells were obtained from the Michigan Cancer Foundation and cultured in the DMEM/F-12 medium originally used to develop the cell line [26]. Human breast cancer ZR75-1 and MCF-7 cell lines were obtained from ATCC and the Michigan Cancer Foundation, respectively, and cultured in a supplemental McCoy's 5A medium containing 10% fetal bovine serum [27]. Retroviral packaging PA317 cells were obtained from ATCC and cultured in DMEM containing 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
“…The spontaneously immortalized human mammary epithelial MCF-10A cells were obtained from the Michigan Cancer Foundation and cultured in the DMEM/F-12 medium originally used to develop the cell line [26]. Human breast cancer ZR75-1 and MCF-7 cell lines were obtained from ATCC and the Michigan Cancer Foundation, respectively, and cultured in a supplemental McCoy's 5A medium containing 10% fetal bovine serum [27]. Retroviral packaging PA317 cells were obtained from ATCC and cultured in DMEM containing 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
“…Aromatase is elevated in most breast cancers [ 32 ] and interestingly in other cancers not typically associated with dysregulated steroidogenesis such as NSCLC [ 33 ] and colon cancer [ 34 ]. Aromatase has even been linked with metastasis [ 35 , 36 ] and transgenic models demonstrate its oncogenicity [ 37 , 38 ], yet many unknowns remain about the diverse pathway(s) that drive CYP19A1 overexpression. This question is important because tumor-associated estrogen production was shown to be significantly higher than levels in the plasma of post-menopausal patients or in normal tissue [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In postmenopausal women, extragonadal sites such as mesenchymal cells of the adipose tissue and skin, bone, and brain express aromatase and become the main source of estrogen. The estrogen produced by breast adipose tissue is strongly implicated in promoting the development and growth of ER-positive breast cancer [12]. Shibahara et al [13] reported that the aromatase status of a primary tumor generally represents the status of metastatic lymph nodes, and aromatase immunoreactivity was detected in the adipose tissue surrounding the lymph node.…”
Section: Discussion/conclusionmentioning
confidence: 99%